Tantangan dan Peluang Perbankan Syariah Dalam Membangun Inovasi Bisnis dan Sustainability di Era Digital - Ainul Yakin , Ikin; Elsa, Elsa; Abdillah, Apip; Savanda, Eva (Banque Syar'i: Jurnal llmiah Perbankan Syariah, 2024)
The development of Sharia finance in Indonesia has grown rapidly, presenting both challenges and opportunities for businesses, particularly banking, to expand their operations to create a sustainable economy for society and the environment in the future. This study employs a qualitative method with a literature review approach to explore the opportunities and challenges faced by Islamic banking in fostering innovation and sustainability in the digital era. Data were collected through literature studies. The findings reveal that Islamic banks in the digital era have opportunities to support banking innovation and develop sustainable finance by implementing the ESG (Environmental, Social, and Governance) framework in alignment with Sharia principles. In this context, Islamic banks can enhance existing programs, such as zakat (almsgiving), sadaqah (charitable giving), and waqf (endowment), as part of their social initiatives to strengthen sustainability in banking. The challenges faced by Islamic banking in fostering Sharia innovation include the still underdeveloped information and communication technology (ICT) infrastructure, which can hinder the delivery of Islamic banking services and limit their reach to remote rural areas.